(untitled) (Religious dialogue and cooperation, 2024)
This paper will strive to address the novel manifestations and roles that sacrilege plays in the postsecular world, and especially how it figuresin the symbolic battles waged in Serbia after October 5, 2000 over which current has the indisputable right to form its postsocialist collective identity – ethnic, ethical, ideological, religious.The focus will be on concrete incidents in Serbian public space involving accusations of blasphemy and the ensuing debates, which have arguably helpedestablish and maintain the symbolic boundaries in a society. The sample includes cases which are mentioned in news portals available online and this corpus of empirical material consisting of media content will be contextualized and subjected to discourse analysis. Of special interest will be the ways in which both accusations of blasphemy and defenses against these accusations can serve to draw lines around respective collective identities in symbolic divisions usually closely corresponding with geopolitical ones. The sociocultural problems that will hopefully be further illuminated are the modalities of the secular status of the state, freedom of religion and freedom of speech, collective identities (most pertinently ethnic nationalism, especially when combined with Eastern Orthodoxy in a postsocialist country), geopolitical influences, and postsecular hybrids (especially establishing which are permissible in a community, and which are perceived as impure mixing and as such sacrilegious).